Numerical Investigation of the Laying of Airbag Arrangements on Launching Barges - Alamsyah,; Gonawan, Christian Hendra; Ikhwani, Rodlian Jamal; Hidayat, Taufik; Habibi,; Suwedy, Wardina (International Journal of Marine Engineering Innovation and Research, 2025)
Ship-launching technology is developing rapidly in an effort to reach a point of economic efficiency, time efficiency, security, and flexibility. On the one hand, risks to the process of launching ships using airbags are still present and can occur. Exploding airbags due to the inability to withstand the load has implications for structural damage. Excessive pressure on the airbags can cause structural deformation. This study aims to determine the effect of airbag pressure on the strength of the ship's structure. This study uses finite element-based software to analyze stresses and deformations in ship construction when interacting with airbags. From this study, it was found that the number of airbags used in the two-row layout and cross-over arrangement was 14, with the status of the airbags in terms of load distribution being safe (not broken). The maximum stress value obtained from the simulation on the two-row arrangement layout is 11.62 MPa when it is right in the frame and 9.83 MPa when it is between frames. As well as in the cross-over arrangement layout, the maximum stress is 20.24 MPa when in the frame and 13.84 MPa when in between frames. This phenomenon occurs because of the stress concentration in the frame.